3D Printing Filament - Atwater, Mark (McGraw-Hill Education, 2018)
This project examines the various factors that influence performance of filament used in extrusion-type additive manufacturing processes. Both thermal and mechanical properties are discussed, including glass transition temperature, melting temperature, thermal expansion coefficient, specific heat capacity, flexural strength, hardness, maximum.